Procedural and longer-term outcomes of wire- versus device-based antegrade dissection and re-entry techniques for the percutaneous revascularization of coronary chronic total occlusions. (15th March 2017) - Azzalini, Lorenzo; Dautov, Rustem; Brilakis, Emmanouil S.; Ojeda, Soledad; Benincasa, Susanna; Bellini, Barbara; Karatasakis, Aris; Chavarría, Jorge; Rangan, Bavana V.; Pan, Manuel; Carlino, Mauro; Colombo, Antonio; et al.
Abstract: Background: There are few data regarding the procedural and follow-up outcomes of different antegrade dissection/re-entry (ADR) techniques for chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Methods: We compiled a multicenter registry of consecutive patients undergoing ADR-based CTO PCI at four high-volume specialized institutions. Patients were divided according to the specific ADR technique used: subintimal tracking and re-entry (STAR), limited antegrade subintimal tracking (LAST), or device-based with the CrossBoss/Stingray system (Boston Scientific, Marlborough, MA). Major adverse cardiac events (MACE: cardiac death, target-vessel myocardial infarction and target-vessel revascularization) on follow-up were the main outcome of this study. Independent predictors of MACE were sought with Cox regression analysis. Results: A total of 223 patients were included (STAR n  = 39, LAST n  = 68, CrossBoss/Stingray n  = 116). Baseline characteristics were similar across groups. Technical and procedural success was lower with STAR (59% and 59%), as compared with LAST (96% and 96%) and CrossBoss/Stingray (89% and 87%; p  < 0.001 for both). At 24-month follow-up, MACE rates were higher in STAR (15.4%) and LAST (17.5%), as compared with device-based ADR with CrossBoss/Stingray (4.3%, p  = 0.02), driven by TVR (7.7% vs. 15.5% vs. 3.1%, respectively; p  = 0.02). Multivariable Cox regression analysis identified wire-based ADR (STAR and LAST) and total stent length as independent predictors of MACE. Conclusions: In this multicenter cohort of patients undergoing CTO PCI with ADR techniques, STAR had lower success rates, as compared with the CrossBoss/Stingray system and LAST. The CrossBoss/Stingray system was independently associated with lower risk of MACE on follow-up, as compared with wire-based ADR techniques.